The Importance of Integrating the Four Language Skills and Its Impact on Student Performance - Gulbahor Tukhtaeva; Pardayeva Aziza (Zien Journals, 2024)
The article provides information about the significance of the immersion and integrations of four major languages skills in EFL (English as a foreign language) classroom. The author thoroughly discusses the efficiency and relevance of implementing all four skills in classroom and its accordance with the enhancement of learners’ performance.
Keywords: skills integration; increased cognitive flexibility; contextualized vocabulary